2009
DOI: 10.1038/oby.2008.638
|View full text |Cite
|
Sign up to set email alerts
|

Neurobehavioral Inhibition of Reward‐driven Feeding: Implications for Dieting and Obesity

Abstract: OverviewThe development of effective weight loss interventions requires a thorough understanding of the motivational factors that drive and inhibit the overconsumption of food. Obesity was once believed to result purely from disruptions of homeostatic mechanisms controlling food intake. However, it is increasingly recognized that much of the excess caloric intake in obesity is driven by pleasure or the rewarding properties of readily available palatable food (1,2). It is important to note that the motivation u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
198
3
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 233 publications
(214 citation statements)
references
References 69 publications
11
198
3
2
Order By: Relevance
“…The current study points out that girls high in RS might be more vulnerable, and may encourage future research to elucidate which prevention approaches are most effective for girls high in RS to timely reverse the unfavorable body composition development. For example, future research may determine if strengthening inhibitory control skills is an effective approach for girls high in RS, since good inhibitory control capacities are suggested to counteract reward-driven behavior (Appelhans, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…The current study points out that girls high in RS might be more vulnerable, and may encourage future research to elucidate which prevention approaches are most effective for girls high in RS to timely reverse the unfavorable body composition development. For example, future research may determine if strengthening inhibitory control skills is an effective approach for girls high in RS, since good inhibitory control capacities are suggested to counteract reward-driven behavior (Appelhans, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…At present one in four adults can be described as obese and it is predicted that, if excessive energy intake that contributes to overweight and obesity, is driven by pleasure or 36 the rewarding properties of readily available energy-dense palatable foods (Appelhans, 2009). …”
mentioning
confidence: 99%
“…Nonetheless, recent research suggests that in addition to the homeostatic system, higher cognitive functions also play an important role in energy regulation [for reviews, see [4,5]]. In fact, human brain imaging studies have revealed that food-related stimuli can activate brain circuits implicated in reward, particularly the orbitofrontal cortex (OFC), insula, amygdala, hypothalamus, striatum and midbrain regions [4] and prefrontal areas essential for executive function including inhibitory control of feeding behavior [6,7]. Furthermore, the central nervous system (CNS) circuitry can be modified by hormonal signals, like insulin, which act in the CNS as regulators of whole-body energy homeostasis through their receptors expressed in the limbic forebrain [see [8] for review, [9,10]].…”
Section: Introductionmentioning
confidence: 99%